Mechanisms of aromatic molecule - Oxygen-containing functional group interactions on carbonaceous material surfaces. (July 2021) - Yu, Qi; Feng, Jingyi; Li, Jie; He, Anfei; Sheng, G. Daniel
Abstract: Surface oxygen-containing functional groups (OFGs) at different sites of carbonaceous materials showed different effects on the normalized monolayer adsorption capacity ( Q BET/A ) obtained from the modified BET model. The OFGs on mesoporous surfaces inhibited the adsorption via the water competition, whereas those on the external surface promoted the adsorption due to the enhanced hydrophobic driving force and electrostatic forces, as analyzed from the adsorption molar free energy. Multiple linear relationships were established between the monolayer adsorption capacity Q BET/A and the amounts of OFGs on mesoporous and the external surfaces ( [O] meso and [O] external, respectively). The properties of aromatic adsorbate compounds, the polar area radio of aromatic molecule to water ( PA ad/w ), and the log K ow together influenced the inhibition or promotion effects of OFGs. These results would allow predictions of adsorption behavior of aromatic compounds on carbonaceous materials on the basis of OFGs parameters. Theoretical calculations and simulations projected the configuration of aromatic molecules being parallel to the graphene sheets of carbonaceous materials. The symmetry-adapted perturbation theory (SAPT) energy decomposition showed that the electrostatic forces intensified with the increase of adsorbate polarity. These analyses revealed that the electrostatic forces were enhanced in the presence of OFGs and that the π-π EDA (electron donor-acceptor) was the main force. Graphical abstract: Image 1 Highlights: OFGs on different sites of CMs had different effects on aromatic compound adsorption. Adsorption was correlated negatively with mesoporous OFGs and positively with external OFGs. Aromatic molecular planes were parallel to the graphene sheets of CMs. The π-π EDA was the main force for aromatic adsorption on graphene sheets of CMs.